A Study on the home environment factors of lupus patients and their families a proposed home-like designed center for lupus care in Davao City - Adlawan, Andrea Faye G.; Ylagan, Myrafe S. (2021)
The success of home as a health care environment is more complicated than just simply modifying the physical attributes of a house to fit the activities and health care needs of its users. For such interventions to occur, it is a fundamental foundation to truly understand the role of the four different factors of a home environment; physical, social, community and health. To develop a system of architectural design guidelines, rooted from the goal of providing an ideal environment that may help alleviate symptoms and provide immediate and long-lasting sanctuary for people diagnosed with Lupus, this study had been conducted.Through participant administered photo-documentation of the physical home environment of Lupus patients, preference survey to both Lupus and non-Lupus diagnosed members of the household, and Key Informants Interview (KII) with patients and medical practitioners handling the chronic illness, major differences on the environmental needs and preferences of Lupus patients and their families were identified. Physical environmental factors such as accessibility, lighting, temperature, and availability of supportive features have adverse medical effects on Lupus patients, due to their sensitivities. Isolation is also opted by patients, brought by psychosocial and health safety reasons. Both community awareness and development of healthcare policies supporting Lupies are sought to bring ease to lives of Lupus patients, as well as their families.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2021